Condução de calor em cadeias de osciladores harmônicos com massas alternadas - Romero Barbieri Solha (2010)
In order to search for nontrivial properties of the thermal conductivity with possible applications in the mechanism of heat flow control, this work address the detailed analytical study of a simple microscopic model. It reviews some results from the literature: mainly chains of harmonic oscillators with Hamiltonian and conservative dynamics, with thermal reservoirs modeled by stochastic noises. As a main result it is shown that, in harmonic chains of oscillators with alternate masses and thermal baths at the boundaries only, the heat flow decays as the inverse of the square of the mass difference, in contrast with the homogeneous chain, where it decays with the inverse of the mass. It recalls some results for the chain with self-consistent inner reservoirs, another model in which a similar behavior of the heat conduction in function of the particle masses occur, in order to show that it may be a general property, valid on various systems.